1976
DOI: 10.1111/j.1570-7458.1976.tb02640.x
|View full text |Cite
|
Sign up to set email alerts
|

INCOMPATIBLE RACES OF EUROPEAN CHERRY FRUIT FLY, RHAGOLETIS CERASI (DIPTER A: TEPHRITIDAE), THEIR ORIGIN AND POTENTIAL USE IN BIOLOGICAL CONTROL

Abstract: International investigations on the unidirectional incompatibility between two races of Rhagoletis cerasi discovered in 1972 have yielded a new distribution map of the observed phenomenon. Genetic, cytoplasmic and symbiote‐induced incompatibility can be proposed as possible mechanisms but increasing evidence indicates that the observed sterility is caused by extra‐chromosomal factors. Three hypotheses are suggested to explain the possible origin and mode of action of the observed trait. The potential use of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
64
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 12 publications
7
64
0
1
Order By: Relevance
“…Casually recorded in 1983, this species was recorded from Switzerland by Merz (1991) as "R. indiff erens", but later was correctly identifi ed as R. cingulata (Boller & Mani, 1994;EPPO, 2004EPPO, , 2010. European specimens oft en have widely darkened mid and hind femora, as well as the wing pattern typical for R. indiff erens.…”
Section: Rhagoletis Bagheeramentioning
confidence: 99%
“…Casually recorded in 1983, this species was recorded from Switzerland by Merz (1991) as "R. indiff erens", but later was correctly identifi ed as R. cingulata (Boller & Mani, 1994;EPPO, 2004EPPO, , 2010. European specimens oft en have widely darkened mid and hind femora, as well as the wing pattern typical for R. indiff erens.…”
Section: Rhagoletis Bagheeramentioning
confidence: 99%
“…However, at the time of this writing, ongoing experimental work suggests that some Brazilian natural populations of medfly may be infected with Wolbachia (D. Selivon, personal communication). To determine whether the medfly can support Wolbachia infections and express CI, we used conventional embryonic cytoplasmic injections (14-17) for transfer of natural bacterial symbionts from a related species, R. cerasi (Diptera, Tephritidae) (18), to an uninfected laboratory strain of medf ly C. capitata (Diptera, Tephritidae), the Benakeion strain.Previous studies have demonstrated high levels of incompatibility between natural populations of R. cerasi (10,19), the basis of which was recently shown to be Wolbachia (18). Populations of R. cerasi are either infected by a single Wolbachia variant, wCer1, or coinfected by two variants, wCer1 and wCer2.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated high levels of incompatibility between natural populations of R. cerasi (10,19), the basis of which was recently shown to be Wolbachia (18). Populations of R. cerasi are either infected by a single Wolbachia variant, wCer1, or coinfected by two variants, wCer1 and wCer2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies demonstrated high levels of incompatibility between populations of R. cerasi (1,2), the basis of which was recently shown to involve Wolbachia (32). Populations of R. cerasi are either infected by a single Wolbachia variant, wCer1, or superinfected by two variants, wCer1 and -2.…”
mentioning
confidence: 99%